Cognitive Workload and Workload Transitions Elicit Curvilinear Hemodynamics During Spatial Working Memory - McKendrick, Ryan; Harwood, Amanda (Frontiers in Human Neuroscience, 2019)
Adaptive training and workload management has the potential to drastically change safety and productivity in high-risk fields - including, air-traffic control, missile defense, and nuclear power-plant operations. Quantifying and classifying cognitive load is important for optimal performance. How cognitive workload changes over time may alter cognition and the perception of workload. Brain based metrics have previously been associated with mental workload. Specifically, attenuation of prefrontal activity has been linked to cognitive overload, a cognitive load state associated with degraded task performance. We hypothesized that a similar nonlinearity would be observed for cognitive underload combining to form a cubic function in lateral prefrontal cortex as a function of working memory load. Two studies were conducted. The first assessed the relationships between spatial working memory load to subjective, behavioral and hemodynamic measures. A cubic function was observed in left dorsolateral prefrontal cortex (LDLPFC; Brodmann’s Area 46) relating working memory load to changes in oxygenated hemoglobin (HbO). The second, two-part study tested the effects of workload transitions to different cognitive load states. Part one replicated the effects observed in study one and identified transition points for individual performers. Part two assessed the effects of transitioning to different cognitive load states. Cognitive load state transitions caused a deviation between behavioral measures and induced a significant change in the cubic function relating LDLPFC HbO and working memory load. Changes in cognitive load cannot account for workload transition effects on behavior and prefrontal activity. We present a hypothesis associating workload transitions with disruption of cognitive process integration.